SISTEM INFORMASI SURAT MENYURAT DI DESA PURWODADI KECAMATAN PURWODADI BERBASIS WEBSITE MENGGUNAKAN METODE WATERFALL - Aviani, Anggi; Pasa, Ike Yunia; Saputro, Wahju Tjahjo (JURNAL AKADEMIKA, 2024)
Management of correspondence administration at the Purwodadi Village Office, Purwodadi District, still uses a manual process, namely using books or paper as a tool to record incoming and outgoing letters. Apart from that, incoming letters (archiving) are still stored manually in filing cabinets. This relates to the security of letters or information that is stored because if it is not managed properly the paper could be damaged or lost. Researchers conducted research and built a website-based correspondence information system at the Purwodadi Village Office, Purwodadi District. This information system was created to make it easier for secretaries to manage correspondence administration. In collecting data, researchers used observation, interviews and literature study methods. Meanwhile, the method used for information system development is Waterfall and the language used in information system development uses the PHP programming language, the Laravel framework, the database used is MySql. The usefulness of the information system developed can provide various facilities such as the process of adding, changing and deleting mail data. Apart from that, the system can produce outgoing letters (introduction) which can be directly saved in PDF form and can be printed immediately.